Clinical assessment of balance and mobility - Franchignoni, Franco (Rehabilitacija (Ljubljana), 2012)
Assessment of balance and mobility in clinical settings can help to determine both risk of falling and the most suitable measures to reduce postural instability. Laboratory studies have shown that postural control embraces different reactions to external disturbances, anticipatory postural adjustments to perturbations caused by self-initiated movements (e.g. lifting an object), and dynamic balance during gait. However, until recently clinical balance tests did not systematically evaluate all these subdomains. In this short review, the most widely used clinical assessments of posture and balance are discussed. Clinical evaluations are divided into four groups: (a) simple clinical tests for balance and mobility; (b) fear of falling and fall-efficacy scales; (c) clinical balance and mobility scales; (d) the new balance and mobility scales: BESTest and its short form, the mini-BESTest. Themini-BESTest is a new 14-item balance measurement tool recently created using both classical psychometric techniques and Rasch analysis. It meets a wide range of measurement requirements (regarding dimensionality, quality of the rating categories, construct validity and reliability indices), focuses on dynamic balance and can be conducted in 10-15 minutes. The scale contains items belonging evenly to: transitions and anticipatory postural adjustments, postural responses to perturbation, sensory orientation while standing on a compliant or inclined base of support, and dynamic stability in gait. In a recent study evaluating balance disorders in Parkinson's disease, the psychometric characteristics of the mini-BESTest compared favourably with those of the Berg Balance Scale.
Keywords: balance; clinical assessment; fall efficacy; fear of falling; klinično ocenjevanje; mobility; premičnost; ravnotežje; strah pred padcem; učinkovitost padca